Prediction of response to chemotherapy by ERCC1 immunohistochemistry and ERCC1 polymorphism in ovarian cancer. Issue 4 (1st July 2008) - Steffensen, K. D.; WaldstrØ M, M.; Jeppesen, U.; Brandslund, I.; Jakobsen, A.
Abstract : The response of tumor cells to platinum-based chemotherapy involves DNA repair mechanisms. Excision repair cross-complementation group 1 (ercc1) is one of the leading genes involved in DNA repair, and several studies have linked ercc1 to platinum resistance in cell lines and in human cancers. A common single nucleotide polymorphism (SNP) of ercc1 at codon 118 has been proposed to impair ercc1 translation and reduce ERCC1 protein expression and consequently influence the response to platinum-based chemotherapy. The primary aim of the present study was to evaluate ERCC1 expression and ercc1 codon 118 polymorphism in epithelial ovarian cancer (EOC) and their possible predictive value in patients treated with platinum-based chemotherapy. Formalin-fixed, paraffin-embedded tissue sections from 159 patients with advanced EOC were used for immunohistochemistry. Ercc1 codon 118 SNP genotyping was performed by real-time polymerase chain reaction. ERCC1 protein overexpression was found in 37.7% of the tumors. The CA-125 response rate was 94.5% (52/55) in patients with ERCC1-negative tumors compared to 80% (36/45) in patients with ERCC1-positive tumors ( P = 0.026, χ 2 ). The T/T genotype (44%) signalized a better response to chemotherapy than C/C (15%) + C/T (41%) variants ( P = 0.045, trend test). Patients with ERCC1-negative tumors appear to have significantly better response to platinum-based chemotherapy compared to patients with ERCC1-positive tumors, but the differences in response rates did not translate into differences in survival. In addition, the TT genotype seems to be favorable toward better response to platinum-based chemotherapy.